Global patterns and drivers of species and trait composition in diatoms. Issue 8 (23rd March 2016) - Soininen, Janne; Jamoneau, Aurélien; Rosebery, Juliette; Passy, Sophia I.
Abstract: Aim: To examine species and trait composition in stream diatoms along environmental, climatic and spatial gradients and to ascertain if the use of different levels of biological organization is beneficial for investigating global environmental changes and the role of history in structuring communities. Location: Global cover with datasets from the Antilles, France, Finland, New Zealand, La Réunion and the United States. Methods: We related diatom species composition, guild composition, total richness and richness across guilds to environmental, climatic and spatial variables. We used non‐metric multidimensional scaling (NMDS) with environmental variable fitting, redundancy analysis (RDA) with variation partitioning, analysis of similarities and linear mixed models as statistical tools. Results: Species composition differed significantly among the study regions, while the differences in guild composition were less pronounced. US and French streams shared a large number of species, whereas islands shared only a few species with continents. For species composition, all predictors showed significant relationships with diatoms but pH, longitude, annual temperature and precipitation had the strongest impact. Variation partitioning revealed that the local environment outperformed climatic and spatial variables. For guild composition, there was a substantial overlap across regions in NMDS. The results from RDA demonstrated, however, that guild composition was better explained than species composition, especially by environmental variables. Both species and guild richness were significantly correlated with most predictors. Notably, species richness scaled positively with latitude. Main conclusions: Diatom species and guild composition varied substantially in response to local environment and climatic and spatial variables indicating both environmental and historical effects. Species composition discriminated the geographical regions better, while guild composition detected the environmental gradients better. This emphasizes the need to examine different levels of organization to gain a deeper understanding of the roles of environment versus history in structuring communities. These findings suggest that diatom species distributions are under strong microevolutionary constraints. Conversely, guild distributions are less dependent on historic factors and are driven primarily by the environment, which makes them better suited for research on global environmental change.